PENGARUH VISI DAN OTONOMI TERHADAP PENGEMBANGAN PENGETAHUAN PADA PERUSAHAAN SWASTA NASIONAL PT. INTERNUSA - Hendratmoko Hendra (Jurnal Manajemen, 2016)
Knowledge to knowledge competition will become top business competition issue in upcoming future. It becomes challenges for PT. Internusa engaged in domestic and international transportation business sector. One of the strategy is to development knowledment in the Company, so that can be expected to produce innovative and competitive services. Issues raised in this research is what factors affecting the process development of knowledge in company and how the on going knowledge development process happened in Internusa especally in Jakarta, Bandung and Cikarang Branches. The purpose of this research is to determine the factors affecting the process development of knowledge in company and how the on going knowledge development process happened in Internusa especally in Jakarta, Bandung and Cikarang Branches. Using regression analysis and qualitative observations resulting that the vision and autonomy have significant influence Against The development process knowledge in Internusa especially in Jakarta, Bandung and Cikarang branches. While the level of competition, information and knowledge diversity do not have a significant influence Against The Knowledge Development process. Meanwhile, knowledge development process is not run well because of system thinking, a shared vision, mental models, personal mastery and team learning not yet running optimally in Internusa especially in Jakarta, Bandung and Cikarang branches..Â Keywords: Vision, Autonomy, Competition, Information, Knowledge Diversity